Subpopulation of Immigrants in Lithuania: Foreign-Born Generations - Stankūnienė, Vladislava; Ambrozaitienė, Dalia; Baublytė, Marė (Lithuanian Journal of Statistics, 2019)
The article analyzes the foreign-born population of Lithuania, its age and ethnic composition, and periods of arrival to Lithuania. The analysis is based on the 2011 Lithuanian Population Census data. The results of the analysis show that the foreign-born population of Lithuania is very heterogeneous and has three major groups formed at different times, by different immigration factors and flows, they are different by age and ethnic composition. Most of foreign-born population of Lithuania is formed during the Soviet era - those who arrived from the former USSR. Among them the majority are of Russians, but a quite large part - Lithuanians who arrived since the mid-sixties of 20th century (children of deportees). The youngest generation of the emerging foreign-born generation is from Western European countries.
Keywords: foreign-born population; immigration; ethnicity; Lithuania